THE DEVELOPMENT OF XINDI PIANO TEACHING METHOD IN TEACHING COLLECTIVE PIANO BEGINNERS IN CHINA - Chupeng, He; Sondhiratna, Thanyawat (Asia Pacific Journal of Religions and Cultures, 2024)
In recent years, there has been a gradual increase in research on the teaching method of the Xindi Piano. Many scholars have conducted in-depth discussions on the teaching philosophy and performance techniques of Xindi from different perspectives. These studies not only involve details of performance techniques, but also provide a comprehensive analysis of Cindy's teaching practice. Through research, we can gain a deeper understanding of the teaching methods and concepts of Sindi, providing theoretical support for further promoting and applying Sindi piano techniques among piano beginners. Teacher Xin Di's piano technique research not only has high artistic value, but also has a profound impact on the entire music education industry. This article presented (1) piano beginner talent cultivation; (2) Xindi piano teaching method; and (3) the development of Xindi piano teaching method in teaching collective piano beginners.